Joseph Wiggins (1832-1905) - Stone, Ian R. (ARCTIC, 1994)
Joseph Wiggins occupies an unusual niche in arctic history. While undoubtedly an explorer, he devoted most of his career in the North not specifically to exploration but to the development of commercial relations between Great Britain and Russia by the exploitation of the sea route to the Ob' and Yenisey Rivers and thence into the centre of Siberia. He was active in the period during which the technological development of ships enabled the route to be practicable for cargo vessels, but before the Russian Revolution closed the route to trade from the West.